Instrumen Inovatif untuk Mengembangkan Asesmen Praktik dan Produk dalam Pembelajaran Bahasa Indonesia di Era Digital - Mutiara Mutiara (Institut Nalanda, 2024)
In the current era of globalization and digitalization, the teaching of the Indonesian language needs to adapt to technological advancements and innovative teaching methods. An important aspect of learning is assessment. Assessment not only measures students’ abilities but also serves as a tool to motivate and guide learning. This article describes various innovative tools that can be used to develop practical tests and learning products for the Indonesian language. Emphasis is placed on the application of digital technology, such as interactive applications and e-learning platforms, and alternative assessment methods, such as collaboration-based projects, digital portfolios, and performance-based assessments. These tools not only enhance student engagement and motivation but also provide more comprehensive and detailed feedback on students’ skills and development. With these innovative tools, it is hoped that learning the Indonesian language will become more meaningful, effective, and enjoyable for students.